Characterizing phenotypic data of Peromyscus leucopus compared to C57BL/6J Mus musculus and diversity outbred (DO) Mus musculus - Lauren A. Wimer; Asia Davis-Castillo; Sofiya Galkina; Serban Ciotlos; Cavan Patterson; Leandro Prado; Maria Castro Munoz; Nicolas Martin; Sharon Epstein; Nicholas Schaum; Simon Melov (GeroScience, 2024)
Translational research is commonly performed in the C57B6/J mouse strain, chosen for its genetic homogeneity and phenotypic uniformity. Here, we evaluate the suitability of the white-footed deer mouse ( Peromyscus leucopus ) as a model organism for aging research, offering a comparative analysis against C57B6/J and diversity outbred (DO) Mus musculus strains. Our study includes comparisons of body composition, skeletal muscle function, and cardiovascular parameters, shedding light on potential applications and limitations of P. leucopus in aging studies. Notably, P. leucopus exhibits distinct body composition characteristics, emphasizing reduced muscle force exertion and a unique metabolism, particularly in fat mass. Cardiovascular assessments showed changes in arterial stiffness, challenging conventional assumptions and highlighting the need for a nuanced interpretation of aging-related phenotypes. Our study also highlights inherent challenges associated with maintaining and phenotyping P. leucopus cohorts. Behavioral considerations, including anxiety-induced responses during handling and phenotyping assessment, pose obstacles in acquiring meaningful data. Moreover, the unique anatomy of P. leucopus necessitates careful adaptation of protocols designed for Mus musculus . While showcasing potential benefits, further extensive analyses across broader age ranges and larger cohorts are necessary to establish the reliability of P. leucopus as a robust and translatable model for aging studies.